2022
DOI: 10.1155/2022/4611331
|View full text |Cite
|
Sign up to set email alerts
|

GLD-Net: Deep Learning to Detect DDoS Attack via Topological and Traffic Feature Fusion

Abstract: Distributed denial of service (DDoS) attacks are the most common means of cyberattacks against infrastructure, and detection is the first step in combating them. The current DDoS detection mainly uses the improvement or fusion of machine learning and deep learning methods to improve classification performance. However, most classifiers are trained with statistical flow features as input, ignoring topological connection changes. This one-sidedness affects the detection accuracy and cannot provide a basis for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…They have introduced two models employing a straightforward DNN architecture and a Convolutional Autoencoder. The authors demonstrated enhanced classification accuracy through the application of DL techniques, achieving an accuracy of 91.9 Guo et al [39] presented GLD-Net, a DL approach that combines topological and traffic features to achieve high accuracy in detecting DDoS attacks. These investigations collectively illustrate the effectiveness of DL in accurately categorizing DDoS attacks.…”
Section: B Deep Learning Approachesmentioning
confidence: 99%
“…They have introduced two models employing a straightforward DNN architecture and a Convolutional Autoencoder. The authors demonstrated enhanced classification accuracy through the application of DL techniques, achieving an accuracy of 91.9 Guo et al [39] presented GLD-Net, a DL approach that combines topological and traffic features to achieve high accuracy in detecting DDoS attacks. These investigations collectively illustrate the effectiveness of DL in accurately categorizing DDoS attacks.…”
Section: B Deep Learning Approachesmentioning
confidence: 99%
“…With this type of classifier ensures centralized attack detection. In 16 , a topological and flow feature-based deep learning method (GLD-Net) was proposed with the objective of extracting the topological features and also employed graph attention network (GAT) for obtaining correlations between non-Euclidean features. Owing to this the average detection accuracy was said to be improved.…”
Section: Related Workmentioning
confidence: 99%